Effects of Panthenol and N-Acetylcysteine on Changes in the Redox State of Brain Mitochondria under Oxidative Stress In Vitro - Dmitry S. Semenovich; Egor Yu. Plotnikov; Oksana V. Titko; Elena P. Lukiyenko; Nina P. Kanunnikova (MDPI AG, 2021)
The glutathione system in the mitochondria of the brain plays an important role in maintaining the redox balance and thiol-disulfide homeostasis, whose violations are the important component of the biochemical shifts in neurodegenerative diseases. Mitochondrial dysfunction is known to be accompanied by the activation of free radical processes, changes in energy metabolism, and is involved in the induction of apoptotic signals. The formation of disulfide bonds is a leading factor in the folding and maintenance of the three-dimensional conformation of many specific proteins that selectively accumulate in brain structures during neurodegenerative pathology. In this study, we estimated brain mitochondria redox status and functioning during induction of oxidative damage in vitro. We have shown that the development of oxidative stress in vitro is accompanied by inhibition of energy metabolism in the brain mitochondria, a shift in the redox potential of the glutathione system to the oxidized side, and activation of S-glutathionylation of proteins. Moreover, we studied the effects of pantothenic acid derivatives-precursors of coenzyme A (CoA), primarily D-panthenol, that exhibit high neuroprotective activity in experimental models of neurodegeneration. Panthenol contributes to the significant restoration of the activity of enzymes of mitochondrial energy metabolism, normalization of the redox potential of the glutathione system, and a decrease in the level of S-glutathionylated proteins in brain mitochondria. The addition of succinate and glutathione precursor N-acetylcysteine enhances the protective effects of the drug.